PEMBERDAYAAN POTENSI KELOMPOK PETANI DENGAN PEMBUATAN KOPI JAHE SEBAGAI UPAYA PENINGKATAN NILAI JUAL PRODUK KOPI - Dewi Handayani; Amrul Bahar; Dewi Jumiarni (Universitas Bengkulu, 2018)
Tapa Gedung village is a village with the majority of the population are farmers. Coffee beans in this village are usually directly sold to buyers without any further processing into coffee powder. The people’s income are still very low. Therefore, the team did a variation dedication and creativity in the coffee beans produced by the community making ginger coffee. Method offered in this proposal is debriefing, direct practice, mentoring, monitoring, evaluation, packaging and marketing. Results of these service activities show that the community is very anthusiastic due to variations in the development of the coffee powder into a coffee flavor of ginger. The selling price of coffee is also increased. Another advantage of coffee products is able to enhance the creativity and people’s revenue. With this program, people become creative to make a variety of products. With the products that are useful and economically valuable, of course will generate revenue for the community, so expect the public revenue that average below the minimum wage could increase at least not under UMR. This program also gave knowledge and expertise (skills) community in the Village of Tapak Gedung in ginger processing and trained about packaging and marketing of coffee ginger product. Keywords: Ginger coffee, Desa Tapak Gedung, Coffee Farmers